Pharmaceutical care for patients with coronary heart disease: transformation of pharmaceutical practice - N. A. Bilousova (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2024)
The implementation of the National Recovery Plan of Ukraine in the field of “Health Care”, namely the restoration of the pharmaceutical sector, improving the population’s access to medicines and their proper use, taking into account the regulatory and legal field harmonized with European legislation, in the context of providing the qualified pharmaceutical care and pharmaceutical services requires application of modern approaches based on evidence-based medicine and implementation in pharmaceutical practice. Patients with cardiovascular diseases, who are provided with medication under the Reimbursement Program and prescriptions from doctors, must be accompanied by pharmaceutical care based on evidence-based medicine to ensure proper use of drugs and rational pharmacotherapy.